Anomalous effects of strain rate on the room-temperature ductility of a cast Mg-Gd-Y-Zr alloy. (15th October 2018) - Li, J.L.; Wu, D.; Chen, R.S.; Han, E.H.
Abstract: The loading rate significantly affects the mechanical properties of Mg alloys. However, the effects of strain rate on newly developed Mg–Gd–Y alloys at room temperature (RT) have rarely been investigated. Here, uniaxial tensile tests were conducted on a cast Mg-10Gd-3Y-0.5Zr (wt. %) alloy (GW103) in both as-aged and as-solutionized states with different grains sizes at RT and various strain rates. The results showed an anomalous positive strain-rate dependence of elongation in all the GW103 alloys investigated from 1 × 10 −5 to 1 × 10 −1  s −1 . Careful microstructural characterization by slip trace analysis revealed that the exclusive deformation mechanism of pyramidal slip, non-Schmid behavior of basal slip, and slip transfer at 1 × 10 −1  s −1 ; these induced the high RT ductility. The occurrence of pyramidal slip activity at high strain rates was suggested to be associated with rare earth solutes, fine precipitates, and local high stresses at grain boundaries due to dislocation pile-up. It was proposed that the increasing strain rate was approximately equivalent to decreases in grain size, enabling the generation of local stresses at grain boundaries, thus causing this anomalous phenomenon. Graphical abstract: The investigations of the anomalous strain rate effect on elongation in a cast Mg-Gd-Y-Zr alloy. Image 1